Pharmacological inactivation of CDK2 inhibits MYC/BCL-XL-driven leukemia in vivo through induction of cellular senescence. Issue 1 (2nd January 2021) - Bazzar, Wesam; Bocci, Matteo; Hejll, Eduar; Högqvist Tabor, Vedrana; Hydbring, Per; Grandien, Alf; Alzrigat, Mohammad; Larsson, Lars-Gunnar
ABSTRACT: Deregulated expression of the MYC oncogene is a frequent event during tumorigenesis and generally correlates with aggressive disease and poor prognosis. While MYC is a potent inducer of apoptosis, it often suppresses cellular senescence, which together with apoptosis is an important barrier against tumor development. For this latter function, MYC is dependent on cyclin-dependent kinase 2 (CDK2). Here, we utilized a MYC/BCL-XL -driven mouse model of acute myeloblastic leukemia (AML) to investigate whether pharmacological inhibition of CDK2 can inhibit MYC-driven tumorigenesis through induction of senescence. Purified mouse hematopoietic stem cells transduced with MYC and BCL-XL were transplanted into lethally irradiated mice, leading to the development of massive leukemia and subsequent death 15–17 days after transplantation. Upon disease onset, mice were treated with the selective CDK2 inhibitor CVT2584 or vehicle either by daily intraperitoneal injections or continuous delivery via mini-pumps. CVT2584 treatment delayed disease onset and moderately but significantly improved survival of mice. Flow cytometry revealed a significant decrease in tumor load in the spleen, liver and bone marrow of CVT2584-treated compared to vehicle-treated mice. This was correlated with induced senescence evidenced by reduced cell proliferation, increased senescence-associated β-galactosidase activity and heterochromatin foci, expression of p19 ARF and p21 CIP1, and reduced phosphorylation (activation) of pRb, while very few apoptotic cells were observed. In addition, phosphorylation of MYC at Ser-62 was decreased. In summary, inhibition of CDK2 delayed MYC/BCL-XL -driven AML linked to senescence induction. Our results suggest that CDK2 is a promising target for pro-senescence cancer therapy, in particular for MYC-driven tumors, including leukemia.